New knowledge and practices to articulate socioculturally diverse knowledge - Zapata-Zapata, Viviana; Quintriqueo-Millán, Segundo; Fuentes-Vilugrón, Gerardo; Morales-Saavedra, Soledad (Edelweiss Applied Science and Technology, 2025)
In a society in constant change, school is a possibility for establishing processes of symmetrical and dialogic relationships between the actors of the educational and social environment in a socioculturally diverse context. For this reason, the articulation of knowledge and actions is presented as a space for relationship-action based on pedagogical and educational practices that are planned and implemented in schools with the involvement of families and the territorial community. The objective of this article is to understand the pedagogical and educational practices that enable the articulation of socioculturally diverse knowledge in the school context. The methodology is educational research from an interpretive paradigm, from the perspective of a multiple case study. The results are explained as follows: 1) The involvement of the family-school-community enables articulation processes with sociocultural relevance; 2) The dialogue of knowledge is an axis for meeting diverse knowledge from the symmetry of power; and 3) The school and the family are agents that must be in permanent dialogue from a language of encounter.